Treatment exit options for non-infectious uveitis registry: participant characteristics at 3 years : inflammation : clinical science - Fink, David; Dell, Jennifer; Heinz, Carsten; Wintergerst, Maximilian W. M.; Höller, Tobias; Berger, Moritz; Schmid, Matthias; Boden, Karl Thomas; Pleyer, Uwe; Reitsamer, Herbert; Deuter, Christoph M. E.; Lohmann, Tibor K.; et al. (British journal of ophthalmology, 2024)
Purpose The Treatment exit Options For non-infectious Uveitis (TOFU) registry documents disease courses for non-anterior non-infectious uveitis entities with and without treatment to generate more evidence for clinical management recommendations including treatment exit strategies. In this article, we present the participants’ baseline characteristics after the first 3 years. - Methods TOFU is an observational, prospective registry and recruits patients ≥18 years of age with non-anterior non-infectious uveitis with or without a history of previous disease-modifying antirheumatic drugs (DMARDs) treatment. The data are collected in the electronic data capture software REDCap and include ophthalmological and general medical history as well as clinical findings. - Results Between 24.10.2019 and 27.12.2022, 628 patients were enrolled at 25 clinical sites in Germany and Austria. Patients with intermediate uveitis were most frequently included (n=252; 40.1%) followed by posterior uveitis (181; 28.8%), panuveitis (n=154; 24.5%) and retinal vasculitis (n=41, 6.5%). At baseline, 39.6% were treated with systemic corticosteroids, 22.3% with conventional synthetic (cs) DMARDs, 20.5% with biological (b) DMARDs and 3.6% with other systemic treatments. Average best corrected visual acuity (BCVA) was 0.69 decimal. Patients with panuveitis had the worst BCVA with 0.63 decimal. Overall, only 8 patients (1.3%) suffered from severe visual impairment. - Conclusions Less than half of participants required DMARD treatment at baseline, with csDMARDs used more frequently than bDMARDs. The presence of severe visual impairment was low, mostly affecting patients with panuveitis. These findings are in line with comparable monocentric cross-sectional studies of tertiary uveitis centres in Germany and will allow us to generate generalisable evidence in TOFU.
Erstmals veröffentlicht: 10. Juni 2024
Gesehen am 25.11.2024